PENGGUNAAN PROBIOTIK KOMBINASI lactococcus lactis DAN L actobacillus acidophilus SEBAGAI PENGGANTI ANTIBIOTIKA PADA AYAM PETELUR YANG DIINFEKSI E scherichia coli TERHADAP ANALISIS USAHA - Hana Cipka Pramuda Wardhani; Widya Paramita Lokapirnasari; Koesnoto Soepranianondo (BUANA SAINS, 2019)
Escherichia coli is a normal flora in the digestive system of laying hens that are non-pathogenic, which can change into pathogens and cause the egg production to decrease. So the combination of Lactococcus lactis and Lactobacillus acidophilus probiotics is expected to be able to overcome E. coli and become a substitute for the antibiotics (Virginiamycin) in animal feed. This study aims to determine business analysis including Break Event Points (BEP), Revenue Cost Ratio (R / C Ratio), Payback Period (PP) and Return On Investment (ROI). The best results obtained for the calculation of Break Event Point (BEP) on a0b2 treatment with a BEP of Rp. 17,587,24 with BEP production on a1b2 of 14,36 kg, Revenue Cost Ratio (R / C Ratio) generates a value of 1,543 for treatment a0b2, Payback Period (PP) generates a value of 1 year 3 months 9 days and Return On Investment (ROI) generates a value of 3. It was concluded that the a0b2 treatment had good results to be developed.